Full band Monte Carlo simulation of AlInAsSb digital alloys. Issue 6 (27th March 2020) - Zheng, Jiyuan; Ahmed, Sheikh Z.; Yuan, Yuan; Jones, Andrew; Tan, Yaohua; Rockwell, Ann K.; March, Stephen D.; Bank, Seth R.; Ghosh, Avik W.; Campbell, Joe C.
Abstract: Avalanche photodiodes fabricated from AlInAsSb grown as a digital alloy exhibit low excess noise. In this article, we investigate the band structure‐related mechanisms that influence impact ionization. Band‐structures calculated using an empirical tight‐binding method and Monte Carlo simulations reveal that the mini‐gaps in the conduction band do not inhibit electron impact ionization. Good agreement between the full band Monte Carlo simulations and measured noise characteristics is demonstrated. Abstract : In this article, we present an initial theoretical study on the low noise AlInAsSb digital alloy APD. Monte Carlo simulations based on band structure calculated using an empirical tight‐binding method fit well with experimental results and revealed the carrier transport properties.